Core-Shell Self-Doped Polyaniline Coated Metal-Organic-Framework (SPAN@UIO-66-NH2) Screen Printed Electrochemical Sensor for Cd2+ Ions. Issue 12 (3rd July 2019) - Zhao, Xiaoyu; Bai, Wenlong; Yan, Yujia; Wang, Yanfei; Zhang, Juankun
Abstract : Cadmium ions have variable degrees of toxicity on the environment and organisms. An electrochemical sensor based on self-doped polyaniline (SPAN) modified Metal-organic Framework (SPAN@UIO-66-NH2 ) with high electron mobility was developed. Cyclic voltammetry and electrochemical impedance spectroscopy indicated that doping of SPAN enhanced the electron transfer rate of UIO-66-NH2 in SPAN@UIO-66-NH2 . The optimized Cd 2+ sensor exhibited good linear response from 0.5 μg L −1 to 100 μg L −1, low detection limit of 0.17 μg L −1 (based on S/N = 3), good stability, and fast response time. It showed decent reliability for detection of trace Cd 2+ in natural lake and urine samples.